Supramolecular assemblies from plant cell polysaccharides: Self-healing and aging behavior. (March 2016) - Roversi, T.; Piazza, L.
Abstract: A fundamental understanding of plant cell wall rheology is essential in view of the formulation engineering of plant-based foods/ingredients. In this paper, by means of oscillatory measurements, we study the rheological behavior of water suspensions of cell wall polysaccharidic supramolecular assemblies, which are extracted with selective solvents precipitation method from apple flesh. Once rehydrated with water, they behave as gel like materials, as it results from the mechanical spectra, with the elastic modulus Gʹ higher than Gʺ within the frequency range considered. Interestingly, amplitude and time sweep measurements show reversible stress softening and stress recovery after high shear strain. The observed behavior of the cell wall molecular assemblies resembles closely to that of colloidal gels, which also display shear-thinning rheological properties and a complex aging response. In this regard, creep measurements indicate history-dependent effects, which are interpreted in terms of aging phenomena, similar to those existing in glassy systems. The self-healing behavior and the non-equilibrium nature we observed allow customized modifications during processing and storage to obtain new structural states and rheology. Such changes in the microstructure might be relevant for product and process performance. Graphical abstract: By means of oscillatory rheology, we report gel-like, self-healing and aging behavior of plant cell walls water suspension. Highlights: Water dispersions of plant cell walls behave as gel-like materials. Dynamic amplitude sweep measurements shows reversible softening. Dynamic time sweep measurements shows stress recovery after shear melting. Creep measurements indicate aging phenomena, similar to those occurring in glassy systems.